Dupilumab therapy improves gut microbiome dysbiosis and tryptophan metabolism in Chinese patients with atopic dermatitis - Yang, Liu; Li, Danqi; Sun, Shuomin; Liu, Danping; Wang, Yi; Liu, Xiaohuan; Zhou, Bin; Nie, Wenjia; Li, Lu; Wang, Yifei; Sha, Shanshan; Li, Yan; et al. (International immunopharmacology, 2024)
[Display omitted] •The gut microbiota is disrupted in patients with atopic dermatitis (AD).•Dupilumab shifts the gut microbial dysbiosis in AD patients to a healthy state.•Improved gut microbiome is associated with upregulated tryptophan metabolism. Dupilumab has demonstrate its potential to orchestrate inflammatory skin microenvironment, enhance skin barrier and shift skin microbiome dysbiosis, collectively contributing to clinical improvement in patients with atopic dermatitis (AD). As the second genome of human body, growing evidence suggests that the gut microbiome might relate to the host response to treatments. Little is known about the association between dupilumab treatment and gut microbiome in AD patients. We aimed to characterize the gut microbiome among Chinese subjects with or without AD and determine the potential effect of dupilumab on the gut microbiome. The 16 s rRNA gene sequencing was conducted on 48 healthy controls (HC), 44 AD patients and 27 AD patients who received dupilumab for 16 weeks. Prior to treatment, we identified the changed beta-diversity, increased Firmicutes/Bacteroidetes ratio, decreased Bifidobacterium and expanded Faecalibacterium among the AD patients compared to HC. After 16 weeks of dupilumab treatment, gut microbiome dysbiosis of the AD patients improved with reversed beta-diversity, closer bacterial connections, increased colonization of Bifidobacterium, Ruminococcus gnavus, and Coprococcus, which were negatively correlated with disease severity indicators. This shift was largely independent of the degree of clinical improvement. Bacterial function analysis revealed further metabolic alterations following dupilumab treatment, including up-regulated expression of genes involved in the indole pathway of tryptophan metabolism, corroborated by quantitative UHPLC-MS/MS analysis. Dupilumab treatment tends to help shift the gut microbial dysbiosis in AD patients to a healthier state, along with improved intestinal tryptophan metabolism, suggesting the gut flora and its metabolites may mediate part of the synergistic therapeutic effects on the host.